The Actor's Mindset: Acting as a Craft, Discipline and Business - Archibald, Craig (Rowman & Littlefield Publishers, 2022)
The Actor's Mindset:Acting as a Craft, Discipline, and Businessuniquely prepares actors to live a full, successful life as a performing artist. While most acting books focus on either the art or the business of entertainment, Archibald looks at the entire picture of what it means to be an actor, focusing on the foundations of both the artist and the entrepreneur to guarantee a complete and fully functioning approach to a career. The Actor's Mindset is divided into three distinct parts: "The Craft," "The Discipline," and "The Business." Archibald's unique experience as both an actor and a coach gives him an unparalleled perspective on the current industry landscape. While classic method texts still circulate, and there are actors who have written books that address craft, none have Archibald's depth of knowledge and experience in coaching, nor approach the art from a professional standpoint instead of solely a teaching one. The success of Craig's approach is exemplified by the success of his clients, a roster that includes Constance Wu, John Slattery, and two-time Academy Award Nominee Dan Futterman.